Portais colaborativos e educação matemática no ensino médio: uma avaliação de atributos e características de portais colaborativos - Ferron, Pedro Maleronka (2008)
The author is proposed at this dissertation, to present an assessment of attributes and characteristics of collaborative portals, used for Mathematics Education, with content targeted to high school. To achieve the proposed work, we tried to select a set of portals, which were chosen, primarily, for their purpose in the field of Mathematics Education. After found examination, was chosen by the choice of nineteen Portals offered by the Internet and used by institutions of public and private education in Brazil and abroad, and foreigners and nine Brazilians in December: four private and five public. The assessment of the portals has been developed from a single methodology for prospecting observed data. In this context, there was a uniformity of information that was deemed necessary to evaluate each portal, aiming, to such a procedure, preventing the addition or deletion of data from them. Based on the theoretical references, it was used as a criterion for assessing the interaction analysis of two categories: the technological and educational, but also of its dimensions most relevant and consistent with the proposal of work. It is important to remember that the two categories, as well as its dimensions do not correspond to areas isolated and separated. They are interlinked and they do this integration allows the portal achieve the purpose for which they are proposing. The aim of the dissertation is to provide indicators on the potential and limitations of various portals evaluated so that help teachers of mathematics, and users, to decide on the appropriateness and their integration into school practices